OC-068 Algorithmic Management of Radiation-Induced Gi Symptoms is Highly Effective: the Orbit Randomised Controlled Trial. (4th June 2013) - Andreyev, H J; Benton, B; Lalji, A; Pennert, K; Lindsay, J O; Gage, H; Norton, C
Abstract : Introduction: Chronic gastrointestinal (GI) symptoms after pelvic radiotherapy are common. Most affected patients never see a GI specialist. We developed a comprehensive algorithm to direct management of new GI symptoms after pelvic radiotherapy. A 3 arm randomised controlled trial was performed to test 2 hypotheses: (1) Algorithm directed intervention is beneficial compared to no intervention (2) outcomes are not worse when patients are managed by a nurse rather than a gastroenterologist. Methods: Patients treated with pelvic radiotherapy > 6 months earlier with persisting GI symptoms were randomised to management according to the algorithm by 1. a GI nurse or 2. gastroenterologist or 3. the self help Macmillan booklet "Pelvic Radiotherapy: Possible Late Effects". After 6 months, booklet arm patients with persisting symptoms could ask to see the gastroenterologist. Patients in the nurse arm were transferred to the gastroenterologist if they had problems beyond the algorithm's scope. The primary end point was change in the modified Inflammatory Bowel Disease Questionnaire – bowel sub score (IBDQ-B) at 6 months. Follow up continued until 12 months. The trial had 80% power to answer the 1st hypothesis after randomising 196 patients and the 2ndafter closing the booklet arm, and randomising 22 more patients to gastroenterologist or nurse. Results: 168 men, median age 70 (range 34 – 83), 50 women median age 61 (29 – 87), 28 treated for GI, 34 gynaecological & 156 urological cancer were randomised to booklet (n = 68), nurse (n = 80) or gastroenterologist (n = 70). 30 (44%) from the booklet and 4 (5%) from the nurse arm crossed to the gastroenterologist. Groups were well balanced for baseline scores and patient characteristics. 66.5% of patients had a baseline IBDQ-B score indicating moderate/severe symptoms. Intention to treat analysis showed a mean improvement in IBDQ-B score in the booklet arm of 4.9 (95% CIs 1.4–8.4), in the nurse arm 8.8 (6.9–11.2) and 10.3 (7.7–13.1) in the gastroenterologist arm. Improvement in IBDQ-B score was both clinically and statistically significant (compared to booklet) in the nurse (p = 0.04), gastroenterologist (p = 0.014) and combined treatment arms (p = 0.006). Outcomes in the nurse treated arm were not worse than those treated by the gastroenterologist (p = 0.428). Improvements were sustained over time. Conclusion: Targeted intervention following a detailed clinical algorithm can significantly ameliorate radiotherapy-induced GI symptoms. Most patients can be managed by a suitably trained and supported nurse. (Funding RfPB, NIHR) Disclosure of Interest: None Declared